Mathematical and Computational Modeling of Metal Ion Release from Cardiovascular Implants - Vrakas, Dimitris (My University, 2024)
In biomedical engineering, ensuring the safety and efficacy of implants through rigorous testing procedures is paramount. The majority of metal alloys used for cardiovascular implants contain high levels of nickel, which, if released in sufficient quantities, can lead to several adverse local as well as systemic effects. To assess general corrosion susceptibility and metal ion release, the US Food and Drug Administration (FDA) recommendations include testing per the American Standard of Testing and Materials (ASTM) F2129-08, F3306-19, and G31-72(2004). Modeling and simulation tools represent a promising approach to improve the nonclinical testing methods employed in the Toxicological Risk Assessment (TRA) of medical devices. This thesis utilizes physics-based equations, stochastic modeling, and computation simulations to complement and supplement the use of in vitro experiments. Physics-based equations will be used as prediction tools on current reported data, which include varying post-processing techniques, varying chemical conditions, application of mechanical stress, and different fabrication methods. Stochastic modeling (Monte-Carlo probabilistic simulations) will address how data are reported in these protocols and their possible use in predictive models. Lastly, computational simulations will be developed to obtain diffusion coefficients and concentration of nickel as these are difficult to measure experimentally. Applying the above shows that post-processing techniques and external factors, such as stress and chemical conditions of immersion, influence nickel ion release. This is evident by the parameters and data fitting predictions obtained by the tested physics-based equations. Parameters are then incorporated into the Monte Carlo simulations to be used as inputs that consist of a range of values, with the ultimate goal of assisting in better nickel release predictions when combined with larger and more complex predictive models. Lastly, computational simulations have proven useful in providing approximate values of diffusion coefficients of nickel in the surrounding medium and surface Ni concentration, both of which are critical to nickel ion release.
Keywords: Vascular Stents; Nickel Ion Release; Regulatory Testing; Numerical Methods; Monte-Carlo Probabilistic Simulations; COMSOL simulation.